Phytochemical Studies of Sonneratia alba and Pharmacophore Modelling Approach towards Antibacterial and Antioxidant Properties - Racheal, James (Universiti Malaysia Sarawak (UNIMAS), 2019)
Sonneratia alba is a mangrove plant from Sonneratiaceae family that has been identify and characterize the bioactive compound from the leaves of Sonneratia alba. The present study also deals with the antioxidant, antibacterial, cytotoxicity and pharmacophore modelling on the leaves of Sonneratia alba. The leaves of Sonneratia alba was collected from Telaga Air, Kuching Sarawak, dried and grounded before phytochemical study was performed. Sonneratia alba leaves were extracted sequentially with petroleum ether, ethyl acetate and methanol. The obtained yield of petroleum ether, ethyl acetate and methanol crude extracts were 1.32%, 2.91% & 4.16%, respectively. Methanol crude extract was subjected to column chromatography resulted in the isolation of two steroid compounds namely stigmasterol and β-sitosterol. Campasterol, ursolic acid and oleanolic acid were all isolated from the ethyl acetate crude extract. The structure of isolated compounds were elucidated and characterized based on the spectral evidence 1H and 13C Nuclear Magnetic Resonance (NMR) Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR) data analysis and comparison with their literature data. Biological assays were carried out on the crude extracts. Three crude extract were subjected to free radical scavenging activity in order to evaluate their antioxidant activity. Antioxidant assay showed that the ethyl acetate and methanol crude extract have high activities with IC50 48.91±0.64 µg/mL and 21.98±0.16 µg/mL, respectively, while weak activity was showed by petroleum ether crude extract with 112.90 ±1.34 µg/mL. While the antibacterial activities were determined using the agar disk diffusion method, against three Gram positive bacteria (Bacillus cereus, Listeria monocytogenes & Staphylococcus aureus) and three Gram negative bacteria (Salmonella typhi, Escherichia coli & Enterobacter aerogenes). The antibacterial assay results showed ethyl acetate and methanol extract appeared to be most effective than petroleum ether extract. Cytotoxicity activity was carried out on all the crude extract using the brine shrimp (Artemia salina) lethality bioassay method to check on the cytotoxicity of these extract. All the pure compound structure, the active molecules were virtually screened using pharmacophore modeling approach in order to identify new lead compounds. It was performed using computer aided drug design (CADD) which was LigandScout 4.1 (software), to find the selective chemical features for antioxidant and antibacterial agents using the ligand-based approach. This study has shown that the Sonneratia alba has high potential to serve as antioxidant and antibacterial compounds that may serve as a lead to the development of new pharmaceuticals. Keywords: Sonneratia alba, stigmasterol, β-sitosterol, campasterol, oleanolic acid, ursolic acid.